Cancer cachexia: more than skeletal muscle wasting - Schmidt, Søren Fisker; Rohm, Maria; Herzig, Stephan; Berriel Diaz, Mauricio (Trends in cancer, 2018)
Cancer cachexia is a multifactorial condition characterized by body weight loss that negatively affects quality of life and survival of patients with cancer. Despite the clinical relevance, there is currently no defined standard of care to effectively counteract cancer-associated progressive tissue wasting. Skeletal muscle atrophy represents the main manifestation of cancer cachexia. However, cancer cachexia is increasingly seen as a systemic phenomenon affecting and/or influenced by various organs. Here, we describe recent developments elucidating the roles of different tissues as well as tissue crosstalk in this wasting syndrome, including potential links to other cancer-associated morbidities. A more comprehensive understanding of cancer cachexia etiology and heterogeneity may enable the development of intervention strategies to prevent or reverse this devastating condition.